The Texan's secret daughter - Navarro, Jolene (Navarro, Jolene. Cowboys of Diamondback Ranch., 2019)
Turning his life around was the hardest thing Elijah De La Rosa ever had to do<U+2014>until his ex-wife, Jazmine Daniels, returns with their young daughter he didn<U+2019>t know existed. Now this successful rancher will do anything to be a good father. But can he forgive himself for the past<U+2026>and turn their second chance into a family for always?